Impact of Eating Speed on Muscle Mass in Older Patients With Type 2 Diabetes: A Prospective Study of KAMOGAWA–DM Cohort - Kobayashi, Genki; Hashimoto, Yoshitaka; Takahashi, Fuyuko; Kaji, Ayumi; Sakai, Ryosuke; Okamura, Takuro; Okada, Hiroshi; Kitagawa, Noriyuki; Nakanishi, Naoko; Majima, Saori; Osaka, Takafumi; Senmaru, Takafumi; et al. (Frontiers in Nutrition, 2022)
Background & Aims: Maintenance of muscle mass is important for sarcopenia prevention. However, the effect of eating speed, especially fast, normal, or slow speed, on muscle mass changes remains unclear. Therefore, the purpose of this prospective study was to investigate the effect of eating speed on muscle mass changes in patients with type 2 diabetes (T2DM). Methods: This study included 284 patients with T2DM. Based on a self-reported questionnaire, participants were classified into three groups: fast-, normal-, and slow-speed eating. Muscle mass was assessed using a multifrequency impedance body composition analyzer, and skeletal muscle mass (SMI) decrease (kg/m²/year) was defined as [baseline SMI (kg/m²)-follow-up SMI (kg/m²)] ÷follow-up duration (year). The rate of SMI decrease (%) was defined as [SMI decrease (kg/m²/year) ÷baseline SMI (kg/m²)] ×100. Results: The proportions of patients with fast-, normal-, and slow-speed eating were, respectively, 50.5%, 42.9%, and 6.6% among those aged <65 years and 40.4%, 38.3%, and 21.3% among those aged ≥65 years. In patients aged ≥65 years, the rate of SMI decrease in the normal (0.81 [95% confidence interval, CI: 2.23 to -0.72]) and slow (0.89 [95% CI 2.45 to -0.66]) speed eating groups was higher than that in the fast speed eating group (-1.11 [95% CI 0.34 to -2.57]). On the contrary, there was no difference in the rate of SMI decrease among the groups in patients aged <65 years. Compared with slow speed eating, the adjusted odds ratios of incident muscle loss (defined as rate of SMI decrease (%) ≥0.5%) due to fast- and normal-speed eating were 0.40 (95% CI 0.17 to 0.93) and 0.82 (95% CI 0.35 to 1.95), respectively. Conclusion: Slow-speed eating is associated with a higher risk of muscle mass loss in older patients with T2DM.